2010
DOI: 10.1088/0953-8984/22/45/454117
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated translocation of polypeptides through a single nanopore

Abstract: The transport of polypeptides through nanopores is a key process in biology and medical biotechnology. Despite its critical importance, the underlying kinetics of polypeptide translocation through protein nanopores is not yet comprehensively understood. Here, we present a simple two-barrier, one-well kinetic model for the translocation of short positively charged polypeptides through a single transmembrane protein nanopore that is equiped with negatively charged rings, simply called traps. We demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 56 publications
(146 reference statements)
4
55
0
Order By: Relevance
“…In this case, the attractive sites are aromatic residues, thus reducing the activation free energies for sugar translocation from one side of the membrane to the other (37). In the past, we also demonstrated that attractive sites present within the channel lumen have major implications even for larger molecules, such as polypeptides traversing the channel (29;38), which is in accord with the theoretical predictions (3942). …”
Section: Discussionsupporting
confidence: 87%
“…In this case, the attractive sites are aromatic residues, thus reducing the activation free energies for sugar translocation from one side of the membrane to the other (37). In the past, we also demonstrated that attractive sites present within the channel lumen have major implications even for larger molecules, such as polypeptides traversing the channel (29;38), which is in accord with the theoretical predictions (3942). …”
Section: Discussionsupporting
confidence: 87%
“…1a right). The K131D 7 pore was previously used by the Movileanu group to trap proteins containing positively charged tags 37, 38 . The nanocarrier used for driving the target nucleic acid into the nanopore contained a polycationic peptide tag (charge +8 e , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S17). For example, in a range of transmembrane potentials between +20 and +80 mV, the dwell time of Syn B2 within the pore interior of FhuA ΔC/Δ5L was between 0.08 and 0.18 ms. A biphasic voltage dependence of the dwell time or rate constant indirectly suggests that the relatively short Syn B2 polypeptide rapidly navigates across the pore interior of FhuA ΔC/Δ5L at potentials greater than a critical value [3638]. The conspicuous lack of the 33% blockades might likely be determined by the rapid Syn B2 translocation.…”
Section: Resultsmentioning
confidence: 99%